(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
The whole world is becoming full of lifestyle disorders. Due to the rapid modernization people are leading more stressful lives. As a result of that modernization hypertension is one of the big world wide spread disorder which comes across in practice. About 26.4% of the world adult population in 2020 had hypertension and 29.2% were projected to have this condition by 2025. India is labeled as global capital of hypertension. Ayurveda can be described as a real science of life. Ayurveda has an upper edge in treating the disease with emphasis on its root cause, where modern medicine is so entrenched in its pharmaceutical based symptoms treatment. The Ayurveda concentrates on achieving the promotion of health, prevention and management of disease for a healthy and happy life in the ailing society. The principals of Ayurveda are focused on maintaining good health by good diet and good lifestyle. In Ayurveda, Hypertension can be correlated with Raktagata Vata and it is consider as Tridoshaja Vyadhi. Treatment for Hypertension in Ayurveda on the basis of aims at balancing of these three Doshas. Proper dietary habits, proper exercise, Yoga, Meditation along with Ayurveda herbs can be beneficial to balancing of mind, which reduce stress and maintain the blood pressure. This article is proved that the planning of proper herbal medications as per Ayurveda guidelines will definitely control the high blood pressure without any hazardous side effects of drugs.